Surface Properties of the Polyethylene Terephthalate (PET) Substrate Modified with the Phospholipid-Polypeptide-Antioxidant Films: Design of Functional Biocoatings - Klaudia Szafran; Małgorzata Jurak; Robert Mroczka; Agnieszka Ewa Wiącek (MDPI AG, 2022)
Surface properties of polyethylene terephthalate (PET) coated with the ternary monolayers of the phospholipid 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), the immunosuppressant cyclosporine A (CsA), and the antioxidant lauryl gallate (LG) were examined. The films were deposited, by means of the Langmuir-Blodgett (LB) technique, on activated by air low temperature plasma PET plates (PETair). Their topography and surface chemistry were determined with the help of atomic force microscopy (AFM) and time-of-flight secondary ion mass spectrometry (TOF-SIMS), respectively, while wettability was evaluated by the contact angle measurements. Then, the surface free energy and its components were calculated from the Lifshitz-van der Waals/Acid-Base (LWAB) approach. The AFM imaging showed that the Langmuir monolayers were transferred effectively and yielded smoothing of the PETair surface. Mass spectrometry confirmed compatibility of the quantitative and qualitative compositions of the monolayers before and after the transfer onto the substrate. Moreover, the molecular arrangement in the LB films and possible mechanisms of DOPC-CsA-LG interactions were determined. The wettability studies provided information on the type and magnitude of the interactions that can occur between the biocoatings and the liquids imitating different environments. It was found that the changes from open to closed conformation of CsA molecules are driven by the hydrophobic environment ensured by the surrounding DOPC and LG molecules. This process is of significance to drug delivery where the CsA molecules can be released directly from the biomaterial surface by passive diffusion. The obtained results showed that the chosen techniques are complementary for the characterization of the molecular organization of multicomponent LB films at the polymer substrate as well as for designing biocompatible coatings with precisely defined wettability.